Profile of hemogram and transaminases in dengue-suspected patients at a first-aid health unit - Érica Maria da Silva; Cristine Vieira do Bonfim; Niedja Maristone de O. Barreto Queiroz; Patrícia Maria Sobral de Oliveira (Universidade Estadual de Maringá, 2015)
Current retrospective analysis describes the laboratorial profile of patients hypothetically diagnosed with dengue at a First-Aid Health Unit in Recife, Pernambuco State, Brazil. Results of hemograms were assessed by counting platelets and transaminase dosages, in the first half of 2012. Further, 394 patients (252 females or 64% and 142 males or 34%) were listed, mostly during March and April. Hemograms with platelet counting was undertaken with 210 patients (53.3%) and hemogram plus transaminases dosages with 184 patients (46.7%). Thrombocytopenia, neutropenia and atypical lymphocytes occurred in both genders. Hematocrits were highest in males and transaminases were more altered in females. Patients attended at the health unit with clinical symptoms of classical dengue had a laboratory profile of non-specific exams which is a feature of infection by the dengue virus. Diagnosis could not be confirmed and the need of a fast test in the health unit services was mandatory. The above avoids dengue cases not being notified and treated or overestimated.